An Overwhelming Burden of Psychosocial Stress: Life With Ischemic Heart Disease for Midlife Patients With Low Socioeconomic Status and Lack of Flexible Resources. (December 2021) - Rasmussen, Amanda Nikolajew; Petersen, Kirsten Schultz; Overgaard, Charlotte
The largest social inequalities in ischemic heart disease are found in the midlife population. These inequalities are often explained by lifestyle factors, while the role of structural factors and psychosocial stress are generally less acknowledged. In this study, we explore the influence of psychosocial stress on life with ischemic heart disease for midlife patients with low socioeconomic status and lack of flexible resources. In-depth interviews were conducted with 18 participants, and a critical hermeneutic approach was used to analyze and interpret data. We found that the participants were exposed to several external psychosocial stressors related to their family relationships, employment conditions, and experiences of stigmatization. These stressors reinforced each other and created an overwhelming burden of psychosocial stress. Our findings call for supportive interventions that target external psychosocial stressors and stressful feelings among this vulnerable group of patients.